NATIONALISM – INTELLECTUAL HISTORY AND PROGRAMMING PRINCIPLES - Bodrožić, Đuro (Political Review, 2023)
Nationalism is based on the principle of the compatibility of political and national unity. The national principle is particularly violated if members of the same nation are divided into several states where they represent the majority in each of them, but none of them can be considered a national staate. A nation that has several states does not have its own nation state. In many cases, it was seen that the relations between such countries are at least fraternal even thought one and the same people live in them. Nationalism requires the matching of ethnic and state borders so that state borders do not cross ethnic borders and separate members of the same nation. Nationalism is laid in the foundations of the modern world, without this teaching it is impossible to understand the history of our world, not only political but also cultural trends in general. Since the Enlightenment and the French Revolution destroyed dynastic legitimcy, the nation became a aource of political legitimacy. This was the reason for many to direct research attention to the idea of the nation and the teaching of nationalism to the historical circumstances in which thi teaching developed and became relevant to the political implications it produced, but also to the intellectual history of nationalism – philosophical aoundations and programmatic settings. This work is contribution to the understanding of the intellectual history of nationalism. Special attention is drawn to Kant's philosophy, in which nationalism found its foothold. From the ideal of autonomy, which in Kant is an ethical imperative for the individual, the philosophy of national self-determination and the collective struggle for the realization of an authentic national will in one's own country emerges when it is applied to groups by Fichte, Schlegel and other Romantics. Giuseppe Mazzini, the apostle of Italian unity, is a person who embodies the ideals of nationalism and patriotism of the nineteenth century. He dedicated his life to the unification of Italy, was sentenced to death twice, and spent his best years in exile. Nationality was an idea in which he saw alvation as a means for the overall transformation of Europe. The national revolution became his mission, he saw all the messianism in the organization of the youth who should carry out the work of liberation. The enormus energy he invested in the realization of the national idea made Mazzini a symbol of the principle of nationality. From Mazzini's teaching, it is clear that nationalism is not only a political program, but a complete view of the world – a worldview.
Keywords: nationalism; national state; politics; legitimacy; Enlightenment; Kant; Mazzini